Correction: The stability of biradicaloid versus closed-shell [E(μ-XR)]2 (E = P, As; X = N, P, As) rings. Does aromaticity play a role?. Issue 17 (20th April 2018) - Grande-Aztatzi, Rafael; Mercero, Jose M.; Ugalde, Jesus M.
Abstract : Correction for 'The stability of biradicaloid versus closed-shell [E(μ-XR)]2 (E = P, As; X = N, P, As) rings. Does aromaticity play a role?' by Rafael Grande-Aztatzi et al., Phys. Chem. Chem. Phys., 2016, 18, 11879–11884.